2015
DOI: 10.1038/srep12155
|View full text |Cite
|
Sign up to set email alerts
|

Transforming berberine into its intestine-absorbable form by the gut microbiota

Abstract: The gut microbiota is important in the pathogenesis of energy-metabolism related diseases. We focused on the interaction between intestinal bacteria and orally administered chemical drugs. Oral administration of berberine (BBR) effectively treats patients with metabolic disorders. However, because BBR exhibits poor solubility, its absorption mechanism remains unknown. Here, we show that the gut microbiota converts BBR into its absorbable form of dihydroberberine (dhBBR), which has an intestinal absorption rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
179
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(187 citation statements)
references
References 33 publications
8
179
0
Order By: Relevance
“…Antibiotics intervention exhibited similar results to previous studies, resulting in a remarkable decrease in gut bacterial diversity and a significant change in bacterial community structure and composition (Feng et al, 2015). Fermented soymilk intake showed no protective effect on the decreased bacterial richness caused by antibiotics intervention, but a slight increase of Simpson index was observed, suggesting an improved bacterial diversity by fermented soymilk consumption.…”
Section: Food Microbiology and Safetysupporting
confidence: 84%
“…Antibiotics intervention exhibited similar results to previous studies, resulting in a remarkable decrease in gut bacterial diversity and a significant change in bacterial community structure and composition (Feng et al, 2015). Fermented soymilk intake showed no protective effect on the decreased bacterial richness caused by antibiotics intervention, but a slight increase of Simpson index was observed, suggesting an improved bacterial diversity by fermented soymilk consumption.…”
Section: Food Microbiology and Safetysupporting
confidence: 84%
“…Although the NR information for some of these bacteria is not available, Enterobacter has been reported to be a NR-producer 28. Indeed, our previous results demonstrated that the Enterobacter cloacae of the gut microbiota efficiently converted BBR to dhBBR 17. Thus, the composition analysis of gut microbiota confirmed the difference of gut flora between healthy subjects and patients with hyperlipidemia which might contribute to the elevated level of NR in intestine.…”
Section: Resultssupporting
confidence: 59%
“…Liquid chromatography with tandem mass spectrometry (LC-MS/MS 8050, Shimadzu Corporation, Kyoto, Japan) and gas chromatography with mass spectrometry (GC-MS QP2010, Shimadzu Cooperation, Kyoto, Japan) were used for the analysis and quantification of BBR and its metabolites in biological samples 14, 17, 20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, oral administration with Bifidobacterium bifidum and L. acidophilus, a probiotic combination, was found to prevent intestinal toxicity in cancer patients who were treated with both cisplatin and radiotherapy (Chitapanarux et al, 2010). In addition to the direct effects on the enzymes and microbiome on the absorption and metabolism of drugs (Maurice et al, 2013;Feng et al, 2015;Montassier et al, 2015), the indirect effects of gut microbiome on the metabolism of drugs were reported to occur through regulation of gene expression and the physiological function of the local mucosal barrier and of distant organs, such as the liver (Bjorkholm et al, 2009;Selwyn et al, 2015;Selwyn et al, 2016).…”
Section: Microbiome: a Key Orchestrator For Cancer Treatmentmentioning
confidence: 99%